CONSERVATION OF HISTORICAL BUILDINGS IN DUTCH COLONILA "CASE STUDY OF THE BUNG KARNO'S EXILE HOUSE BERASTAGI" - Andriana, Melly; Anisah, Siti; Bachtiar, Ramayana (Proceeding International Conference of Science Technology and Social Humanities, 2022)
Historic buildings are icons that reflect the nation's history. Bung Karno's Guesthouse is one of the Dutch colonial heritage buildings which became Bung Karno's hiding place during the Dutch colonial period. The building, which is located in Laugumba village, Berastagi city, Tanah Karo district, has become one of the icons of colonial history in North Sumatra province. The layout of the location of the building in the tourist area makes the hidden building one of the historical tourism icons. The basic problem that occurs in the building and raised in this study is the age of the building which is very old and not maintained has the potential for damage to the building. The condition of the building was not maintained and left alone so that many of the building ornaments were damaged. The pattern of conservation of historic buildings that are less effective has an impact on the destruction of the nation's historical values, this also has an impact on decreasing the number of tourists visiting these places. Another problem that occurred in the Bung Karno Guesthouse building was that the application of the electrical installation system under review did not meet the standardization of the General Electrical Installation Regulations, which should be an important part of the safety and conservation of buildings, especially historic buildings. This rationale is supported by the condition of the building that was damaged, and the existing condition of the electrical installation system which still uses the Dutch colonial era installation system that is more than 80 years old which is one of the indicators so that this research is very important to carry out.